Effectiveness of Terminalia chebula on halitosis among 18-25 years old adults: a randomized controlled trial - Divyadharshini, Murugan; Kavinaya, Thiyagarajan; Haritha, Venkateshkumar; Karthikayan, Ravi; Prasad, Vishnu (International Journal Of Community Medicine And Public Health, 2026)
Background: Halitosis, commonly known as bad breath, is a dental condition characterized by an unpleasant and offensive odour from the oral cavity. Pathological halitosis is mainly caused by Gram-negative bacteria in the oral cavity that produce volatile sulphur compounds (VSC). Chlorhexidine mouthwash has been used for decades; however, it remains contraindicated due to its side effects. On the other hand, the anti-bacterial properties of plant-derived compounds are well documented. The study aims to assess the effectiveness of Terminalia chebula as an oral rinse against VSC in halitosis patients. Methods: The study sample was selected from patients attending the regular outpatient Department of Public Health Dentistry, Karpaga Vinayaga Institute of Dental Sciences and consisting of 30 adults (both males and females) ranging between 18-25 years of age. The sample was selected from people who present with halitosis. The subjects were randomly divided into groups A and B with 15 adults in each group. Group A was assigned to Terminalia chebula mouthwash and group B to chlorhexidine mouthwash. Results: The study demonstrated a significant reduction in halitosis scores and oral hygiene index (OHI) scores post-intervention in both groups, with group A showing a greater improvement. Statistically significant differences were observed between the groups after the intervention for halitosis and OHI scores, while no significant differences were noted at baseline. Conclusions: Terminalia chebula can suitably be used as an oral rinse for halitosis and does not have any side effects such as erosion and staining.